PEMBERIAN PUPUK LIMBAH CAIR BIOGAS DAN PUPUK N TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Adiwijaya, Yuni Anggar; Armaini, Armaini; Venita, Yunel (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research is to know the influence of biogas liquid waste, the effect of N fertilizer and the interaction of the combination of biogas liquid waste fertilizer with N fertilizer, and to determine the dosage of biogas liquid waste, N fertilizer and combination of biogas liquid waste fertilizer with N fertilizer that can increase the production of plants mustard. This research was conducted experimentally using Randomized Block Design (RAK) which was arranged in factorial that consist of 2 factors.The first factor is the provision of biogas wastewater, L1 = Liquid waste fertilizer biogas 1 liter / m2, L2 = Liquid waste fertilizer biogas 3 liters / m2, L3 = Liquid waste fertilizer biogas 6 liters / m2, The second factor is the application of N fertilizer, U0 = No N fertilizer, U1 = N fertilizer 11.5 kg / ha equivalent to urea 25 kg / ha, U2 = Fertilizer N 23 kg / ha is equivalent to urea 50 kg / ha, From the above treatment, 9 combinations were obtained. Each experimental unit was repeated 3 times to obtain 27 experimental units and each unit of experiment was 20 plants, and 4 plants were taken as samples. Keywords: Biogas liquid waste, N and mustard greens